RELASI KONSTITUSI DENGAN USAHA TANI IKAN, SAYUR, TELUR ORGANIK DAN NON-ORGANIK GUNA MENDUKUNG EKONOMI MASYARAKAT DAN WILAYAH ( STUDI KASUS DI KECAMATAN BANTUR KABUPATEN MALANG ) - Sri Muljaningsih; Ghozali Maski; Devanto Shasta Pratomo (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2011)
Agribusiness is still the pillar for farmers’ economy in Indonesia who, mostly, workfor agricultural sector. This also applies in regional economy in which agriculturalsector is the primary sector that becomes the basis for economy and gives sufficientcontribution to the regional economic development. However, the condition of thefarmers’ economy has so far shown no significant development. The Constitution(UUD 1945) regulates national economy that embraces any fields, including the sus-tainable and environment-oriented agriculture, aiming at society’s prosperity in botheconomy and health. The research shows that there is no difference on benefit betweenorganic and non-organic agribusiness on fish, vegetable, eggs. Thus agribusiness isbetter developed conforming to the Constitution that signals environment-orientedagriculture.Keywords: agribusiness, constitution, economic basis, environment-oriented.